Quality Evaluation of Ethiopian 100% Cotton Carded Ring Spun Yarn with Respect to USTER Standards - Biruk Fentahun Adamu; Desalegn Atalie; Erkihun Zelalem Liyew (Journal of Engineering)
Yarn quality influences both fabric production processes efficiency and export market. One method used to gauge competitiveness of an industry is to study its product quality. The aim of this research work is to evaluate the quality of Ethiopian textile spinning mills’ 100% cotton carded ring spun yarns in terms of its evenness (coefficient of mass variation, CVm), imperfections (thick and thin places, neps), and tensile properties with USTER Statistics 2018. Five spinning mills (B3, A0, A2, A4, and K3) of 15N, 20Ne, 25Ne, 30Ne, 35Ne, and 40Ne nominal yarn counts have been selected for the study. The yarn evenness and imperfections were measured using USTER tester 5 and tensile using a STATIMAT tester. The USTER statistical results showed 20.3Ne (mill B3), 32Ne (mill A4), and 36.2Ne (mill A2) had better overall quality, respectively. It was observed that most selected spinning mills had low evenness, imperfections, yarn strength, and good yarn elongation. Tensile properties of A2 (32.85Ne and 36.2Ne) had fallen under 5% USTER statistics percentile which indicates excellent yarn strength. Generally, from studied mills, it was seen that 61.5% of cotton yarn CVm and thin places falls at above 95% and 15% of yarn tenacity falls at ≤5% of Uster statistical percentile.